Cataloguing basics - Suja', Balqis (2005)
This is a one day course for library assistants from community colleges, mostly without prior knowledge or exposure to cataloguing but were almost single handedly managing the library. The session aims at providing elementary knowledge and understanding on bibliographic concepts and principles, what is a catalogue, why catalogue, what is cataloguing, how to catalogue print and media materials, and catalogue and collection organization. Participants were provided with guide containing excerpts of relevant pages from AACR2, MARC outlines, forms of catalogue and authority card, guides to assign DDC notation, guides to assign Sears subject headings, and guides to file card catalogue. There was very limited hands on available, and it was done in group.